Using police crash databases for injury prevention research – a comparison of opt‐out and opt‐in approaches to study recruitment - Elkington, Jane; Stevenson, Mark; Haworth, Narelle; Sharwood, Lisa (Australian and New Zealand journal of public health, 2014)
The study aimed to examine the difference in response rates between opt‐out and opt‐in participant recruitment in a population‐based study of heavy‐vehicle drivers involved in a police‐attended crash. Two approaches to subject recruitment were implemented in two different states over a 14‐week period and response rates for the two approaches (opt‐out versus opt‐in recruitment) were compared. Based on the eligible and contactable drivers, the response rates were 54% for the opt‐out group and 16% for the opt‐in group. The opt‐in recruitment strategy (which was a consequence of one jurisdiction's interpretation of the national Privacy Act at the time) resulted in an insufficient and potentially biased sample for the purposes of conducting research into risk factors for heavy‐vehicle crashes. Australia's national Privacy Act 1988 has had a long history of inconsistent practices by state and territory government departments and ethical review committees. These inconsistencies can have profound effects on the validity of research, as shown through the significantly different response rates we reported in this study. It is hoped that a more unified interpretation of the Privacy Act across the states and territories, as proposed under the soon‐to‐be‐released Australian Privacy Principles1 will reduce the recruitment challenges outlined in this study.